PENGENDALIAN PERSEDIAAN BAHAN BAKU TIMANGAN IKAT PINGGANG JENIS MATIC KECIL DENGAN METODE FORECASTING DAN ECONOMIC ORDER QUANTITY (EOQ) DI UD. SENENG DAMAI - Nuriyanto; Juhriyah (Department of Industrial Engineering - Universitas Yudharta Pasuruan)
During this time, UD. Seneng Damai made a purchase of raw material by just guessing when the amount of goods in the warehouse is running out. This research is expected to help the company to consider and determine the policy in inventory control activities in order to run more effectively and efficiently. So by applying EOQ method, UD. Seneng Damai will know how much order (order quantity) of raw materials buckles and when should the company to re-order raw material buckles during period 2018. Research type used is descriptive research with quantitative approach. Sources of data in this study using secondary data sources obtained directly from the company. Data collection using interviews and documentation. Data analysis used in this research is using Economic Order Quantity method. The results of the analysis prove that if the company applies methods Economic Order Quantity in 2018 in the optimal purchase of raw materials, there is a difference in savings expenditures total costs for raw materials of Rp. 150.305, -. Based on the results of the analysis, it should be UD. Seneng Damai applies Economic Order Quantity method in determining the optimal quantity of raw material purchase, so it can minimize the total cost incurred by the company every year.